Performance Analysis of Sharia Banking Using The Educatian Prism Method: Case Study Pt. Bank Muammalat Sumatera Utara - Atika Atika; Saparuddin Siregar; Sugianto Sugianto (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Using the performance prism method, this study aims to determine and analyze the performance of Islamic banking at PT. Bank Muammalat. The Performance Prism method is a performance measurement model that depicts organizational performance as a three-dimensional shape (prism) with five sides. This model considers satisfaction, stakeholder contribution, process, and company capability in addition to strategy. This is a quantitative study with a descriptive approach. The results showed that PT. Bank Muamalat performance is already good, as evidenced by the overall Total Index value of 6.2331. Whereas a score of 6-7 indicated that the resulting performance was good according to the provisions of the OMAX Achievement Target.